Morality, Ethics, and Values Outside and Inside Organizations: An Example of the Discourse on Climate Change - Besio, Cristina 19XX-; Pronzini, Andrea (2014)
The public debate on climate change is filled with moral claims. However, scientific knowledge about the role that morality, ethics, and values play in this issue is still scarce. Starting from this research gap, we focus on corporations as central decision makers in modern society and analyze how they respond to societal demands to take responsibility for climate change. While relevant literature on business ethics and climate change either places a high premium on morality or presents a strong skeptical bias, our sociological model depicts morality as an indeterminate force: it can lead to both workable solutions or merely reinforce the status quo, depending on what different corporations make of it. We describe, on the one side, the diffusion of moral values in the media discourse on climate change and, on the other side, the specific responses of corporations. While the media discourse generates a pressure on corporations to act responsibly, their moral claims do not provide clear advice for action. As a result, morality becomes available to organizations as a medium that can be re-specified according to their internal dynamics. Corporations transform moral values into something compatible with their own structures through a variety of different responses: introducing formal ethical structures (e.g., codes of conduct), initiating value-oriented projects, or developing informal moral norms, and so on. In some occurrences, morality becomes a mere façade, while in others it serves as a decision-making criterion and deeply influences core activities in firms.
Keywords: Morality; Mass Media; Decision Making; Organizations; Climate Change